Correlation of Sunlight Intensity and Output Voltage on Collector Plate-based Cascaded Thermoelectric Generator Modules - Djafar, Zuryati; Halim, Abdul; Mustofa, Mustofa; Latif, Lita Asyriati; Piarah, Wahyu Haryadi (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The intensity of solar energy is an important factor in viewing the performance of the thermoelectric generator (TEG). Most studies only look at the effect of treatment on the TEG module in the form of cooling mode and its materials. Therefore this study examines the effect of the solar intensity value on the magnitude of the module voltage. On the hot side of the module are placed heat absorber plates of copper, Fe and aluminum plates as well as non collector plates. Modules are cascaded and connected in series as many as 14 modules per plate, so that a total of 56 TEG modules are used. Data collection is carried out simultaneously on all plates. The test results show that the increase in solar intensity is liner with the magnitude of the TEG module voltage or in other words the correlation is positive. The data also shows that copper collector plates produce the highest voltage difference, followed by Ferro, Alumina and no-plates at âˆ†V 0.871, 0.805; 0.369 and 0.153 V, respectively